(3dWGFa GdETGQGJ aj CSQGQ GdMQha GdYdhjGJs - (3CMeO Hf Ydj Hf jhSa, CHh GdYHGS GdHhfj,J (B622 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj COGQ HjO GdCSQGQ dWGFa CadGc GdedchJjGJ s
(3BNQgG (B:s
(3hcTa Gddg JYGdi dge CSQGQ hajg GdJVYja Edi eG fMf HUOOg abO NQLfG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B174 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B25s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1551s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMQha h GdChaGbs